Does quality make a difference? Employment effects of high- and low-quality start-ups - Michael Fritsch; Alexandra Schroeter (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper investigates the impact of new firms' quality on the magnitude of their employment effects. Our results clearly show that the quality of start-ups, measured by their affiliation with sectors and innovative industries, strongly influences the direct and the overall employment contribution of new firms. In particular, start-ups in manufacturing industries generate larger direct and overall growth effects than those in services. Moreover, new businesses in innovative manufacturing and in knowledge-intensive service industries make a larger direct contribution to employment than start-ups affiliated with other industries. We also find a relatively strong overall effect of new business formation in knowledge-intensive service industries. However, the impact of start-ups in innovative manufacturing industries on overall regional employment growth is not statistically significant, which may be mainly due to their rather small share in all start-ups and because they impact more on firms and employment in other regions than do start-ups in non-innovative manufacturing. Finally, we discuss the implications for entrepreneurship policy that can be derived from our findings.
Keywords: L26; M13; O1; O18; R11; 330; entrepreneurship; new business formation; innovative industries; regional development; entrepreneurship policy; Unternehmensgründung; Unternehmer; Branche; Innovation; Beschäftigungseffekt; Deutschland